Experimental investigation on cooling performance of multi-split variable refrigerant flow system with microchannel condenser under part load conditions. (25th April 2015) - Meng, Jianjun; Liu, Min; Zhang, Wenqiang; Cao, Rui; Li, Yajun; Zhang, Hua; Gu, Xiaoyu; Du, Yong; Geng, Yankai
Abstract: On the basis of a 12.5 kW multi-split variable refrigerant flow (VRF) system, the nominal cooling capacity ratio ( θ ) and the COP of the baseline system with fin-tube heat exchanger (FTHX) and the VRF system with microchannel heat exchanger (MCHX) were obtained for different part load ratios (PLRs). The key control strategies of the VRF system were presented. The charged amount of refrigerant ratio β and the pressure drop Δ P of the MCHXs were also achieved. The experimental results show that the β of the MCHXs was decreased by 26.67–46.67% and the optimum charged amount of refrigerant of a VRF system with an MCHX should obtain a discharge pressure between 3.0 MPa and 3.15 MPa for PLR round 100%. The VRF system with the MCHXs obtained large Δ T HX to avoid refrigerant flashing expansion in long pipe application and it could provide residents with better thermal comfort in hot seasons or regions. Highlights: We experimentally exam the cooling performance of commercial VRF system with MCHX. We present the key control strategies of the commercial VRF system. P d locates between 3.0 MPa and 3.15 MPa for PLR round 100% with an optimum M f . MCHX is more suitable to be employed in VRF system with long pipe than FTHX. MCHX in VRF system with supplies larger Q c than FTHX for high temperature condition.